PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN DEPOT ISI ULANG AIR GALON ANDERE - ., Sahyunu; ., Surlan; ., Safuruddin (Sultra Journal of Economic and Business, 2020)
This study aims to determine the service quality of the Andere Gallon Water Refill Depot, Angata Sub-district, South Konawe Regency to customer satisfaction. The type of this study is a quantitative descriptive. Data collection techniques carried out through literature study and field research in the form of observations, questionnaires, agency data, and documentation. The number of samples used 100 people chosen at random. The analytical method used Linear Regression method. The results of this study showed that the service quality indicator at the Andere gallon water refill depot, Angata Sub-district, South Konawe Regency was good because of high percentage, especially the responsiveness indicator (responsiveness). Customer satisfication at the Andere gallon water refill depot, Angata Sub-district South Konawe Regency was good because the quality of service was higher than customer satisfication which means customers of the Andere water refill gallon, Angata Sub-district of South Konawe regency was very satisfied about the service. Effect of service quality to customer satisfaction, from the regression model the result was obtained significant.